Personality Cults from a Communicative Standpoint - Postoutenko, Kirill Jurʹevič (Religions, 2022)
Drawing upon a wide variety of personality cults in religion, culture and politics from Ancient Egypt to our times, the author attempts to present a summary view of this phenomenon from a communicative standpoint. Personality cult is seen as an attribution of universal and eternal socio-cultural significance to certain beings, messages and interaction scenarios in defiance of changes in and diversity of the surrounding reality. The communicative implementation of such a cult involves the suspension of some of the most basic mechanisms of social coordination. Thus, deification of political, cultural or religious leaders eliminates the subordination of individuals to their social roles, whereas canonization severs the ties of certain selected texts with the contexts of their production and reception. Last, but not least, random signaling between the subject of cultic adoration and his or her subordinates runs counter the standard cooperation rules in interaction (‘turn-taking’). Illustrating these points, the article points out at specific communicative pathologies accompanying personality cults and jeopardizing the stability of their socio-cultural environments.